2017
DOI: 10.1016/j.fuel.2017.08.106
|View full text |Cite
|
Sign up to set email alerts
|

Developing techno-economically sustainable methodologies for deep desulfurization using hydrodynamic cavitation

Abstract: The present work, for the first time, describes the efficacy of the cavitation process and compares the cavitation yield for two types of cavitation devices-one employing linear flow for the generation of cavities and other employing vortex flow. The process involves preprogrammed mixing of the organic and aqueous phases, and can be carried out using simple mechanical cavitating devices such as orifice or vortex diode. The process essentially exploits in situ generation of oxidising agents such as hydroxyl rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…One of the most widely investigated application of hydrodynamic cavitation is wastewater treatment (see Ranade and Bhandari, 2014 and references cited therein;Gagol et al 2018). Several other applications of cavitation have also been reported (Carpenter et al 2017;Suryawanshi et al, 2017Suryawanshi et al, , 2018Ranade et al, , 2016Pathania et al 2018 and references cited therein). Hydrodynamic cavitation offers several advantages such as no additional chemicals (clean tech), compact and in-line reactors and low costs.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…One of the most widely investigated application of hydrodynamic cavitation is wastewater treatment (see Ranade and Bhandari, 2014 and references cited therein;Gagol et al 2018). Several other applications of cavitation have also been reported (Carpenter et al 2017;Suryawanshi et al, 2017Suryawanshi et al, , 2018Ranade et al, , 2016Pathania et al 2018 and references cited therein). Hydrodynamic cavitation offers several advantages such as no additional chemicals (clean tech), compact and in-line reactors and low costs.…”
Section: Introductionmentioning
confidence: 90%
“…Ranade et al (2016Ranade et al ( , 2017 have disclosed vortex based devices for cavitation (VoDCa) which can shield the cavities from the reactor walls and can overcome the limitations of conventional hydrodynamic cavitation (HC) devices. Recent studies report several advantages of VoDCa over cavitation reactors based on orifice or venturi (see for example, Suryawanshi et al 2017;. VoDCa are now commercially available and have been deployed at scales up to 50 m 3 /hr (www.vivira.in;Utikar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on applications of these vortex devices for variety of applications [22] , [30] , [34] , [33] . The device has shown significantly better cavitation performance compared to the conventional devices such as orifice [34] .…”
Section: Introductionmentioning
confidence: 99%
“…process, whereas the second one pertains to intraparticle diffusion on the surface of the adsorbent due to the presence of micropores [3]. However, in the case of PP and Ni@PP following three-stage adsorption processes, the first straight line shows immediate adsorption which is due to the presence of active surface sites and the high concentrations of DBT.…”
Section: (7)mentioning
confidence: 98%
“…SO X in air is also associated with various health issues, such as irritation of the nose, throat and eyes, and cough, while a higher level is linked with asthma, bronchitis, and heart disease [2]. According to the US Environmental Protection Agency (EPA), and governments worldwide, the concentration of sulfur is limited to less than 30 ppm for gasoline and 15 ppm for diesel [3]. New regulations demand further limiting of these figures.…”
Section: Introductionmentioning
confidence: 99%